A Settler Colonialism Induced Feminist Snap: A case study in IRS denialism and institutional violence in Canada - Hodes, Caroline (Feminist Asylum: A Journal of Critical Interventions, 2023)
In this study, I preface the analysis of a case study about the IRS (Indian Residential School System) denialism and ableist, misogynist abuse by locating my experience as feminist research demands. I focus on the IRS denialism I witnessed at the University of Lethbridge and my subsequent correspondence with the university administration through discourse analysis.